2018
DOI: 10.1111/mmi.13900
|View full text |Cite
|
Sign up to set email alerts
|

sRNA41 affects ribosome binding sites within polycistronic mRNAs in Methanosarcina mazei Gö1

Abstract: Several noncoding RNAs potentially involved in nitrogen (N)-regulation have been detected in Methanosarcina mazei, however, targets have been identified only for one of them. Here, we report on the function of sRNA , highly expressed under N-sufficiency. Comprising 120 nucleotides, sRNA shows high sequence and structural conservation within draft genomes of numerous Methanosarcina species. In silico target prediction revealed several potential targets, including genes of two homologous operons encoding for ace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 54 publications
(88 reference statements)
0
33
0
Order By: Relevance
“…In contrast, they also showed that loop 2 of sRNA154 contains anti-ribosome binding site (RBS) sequences that masked the RBS of the glnA2-mRNA target, repressing translation initiation [2]. Another sRNA in M. mazei, sRNA41, was also found to repressed its targets at the translation level by masking ribosome binding sites within polycistronic mRNAs [13]. Other molecular mechanisms have been identified in the archaea such as the binding of itsRNAs to the 3'UTR of mRNA targets in S. solfataricus [34] and, more recently, in H. volcanii (Kliemt, Jaschinski, and Soppa, unpublished data).…”
Section: Best Methods For Srna Discoverymentioning
confidence: 98%
See 4 more Smart Citations
“…In contrast, they also showed that loop 2 of sRNA154 contains anti-ribosome binding site (RBS) sequences that masked the RBS of the glnA2-mRNA target, repressing translation initiation [2]. Another sRNA in M. mazei, sRNA41, was also found to repressed its targets at the translation level by masking ribosome binding sites within polycistronic mRNAs [13]. Other molecular mechanisms have been identified in the archaea such as the binding of itsRNAs to the 3'UTR of mRNA targets in S. solfataricus [34] and, more recently, in H. volcanii (Kliemt, Jaschinski, and Soppa, unpublished data).…”
Section: Best Methods For Srna Discoverymentioning
confidence: 98%
“…Most recently, another M. mazei itsRNA, sRNA41, was found to be down-regulated during nitrogen limiting conditions. Targets of sRNA41 were involved in acetyl-CoA-decarbonylase/synthase complexes (ACDS) and were repressed at the translational level [13]. Thus sRNA41 was predicted to play a role in repressing ACDS protein levels, however, under nitrogen limiting conditions, sRNA41 was down-regulated, thus allowing ACDS levels to increase, which in turn provided sufficient amino acids for nitrogenase synthesis and energy for N2-fixation [13].…”
Section: Gene Regulatory Network and Srnasmentioning
confidence: 99%
See 3 more Smart Citations